Testing the Satisfiability of Z Formal Specifications by Using Prolog - Mohd Zin, Abdullah; Shukur, Zarina (Malaysian Journal of Computer Science, 2004)
Formal specifications are now being used as a basis for communication, design, testing and verification of a software product. For a formal specification to be used effectively, it must be valid, which means that it must be well-formed and reflects the user requirements. The normal technique for validating a formal specification is by using formal reasoning. However, the use of formal reasoning is extremely tedious and time consuming. In this paper we explore alternative techniques for validating a Z formal specification. In particular, we consider the concept of satisfiability as a weaker alternative to validity and discuss how testing can be used to check the satisfiability of a Z formal specification.